IMPLEMENTASI MANAJEMEN BANDWIDTH MENGGUNAKAN METODE PEER CONNECTION QUEUE PADA MIKROTIK - Mariyanto, Mariyanto; Maslan, Andi (Computer Science and Industrial Engineering, 2023)
A hotspot consists of one or more WLAN or Wireless LAN Access Points of standard 802.11a/b/g that provide a restricted area in which users can freely join Access Points with WLAN-enabled mobile devices. With advances in technology, a router is a device that is used to perform the routing process. However, since routers are expensive, there are hardware alternatives such as Mikrotik. Mikrotik RouterOS is an operating system that can turn a computer into a router, or often called a PC Router. solutions to take advantage of bandwidth management and use Mikrotik router boards as a tool to divide bandwidth evenly. Because excessive use will cause a long load when accessing the internet or limited bandwidth. To distribute the load and manage the client connection path to a service on the server, the PCQ (Peer Connection Queue) method is used. The way to do PCQ is to upload with type pcq-dpwnload-phd, set the queue size and total queue size, and check the classification list for different addresses. In addition, to implement bandwidth management with PCQ for uploads, you must create the type pcq-upload-pd, set the queue size and total queue size, and check the classifier list for the source address. For setting upload and download targets on the proxy, you must point to the network address 192.168.100.0/24, with a maximum upload speed of 10 MBPS and 30 MBPS download. The results of this study indicate that the use of a PCQ-based proxy network can be applied properly for Pizza Hut delivery in Batam City.